1989
DOI: 10.1037/0022-3514.57.6.1015
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing elation, gladness, and joy.

Abstract: On the basis of a structural analysis of the emotions, descriptive items were created that were postulated to discriminate between elation, gladness, and joy. The items described the situation of each emotion, the different ways in which the body was transformed, the propensity to behave in particular ways, and the different manner in which the emotions functioned to improve the person's life. In the first study, the items were given to subjects who had been asked to recall an instance of elation, gladness, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 18 publications
3
61
0
5
Order By: Relevance
“…A less activated positive emotion, for example, might signal the target's satisfaction with the status quo (Bindl, Parker, Totterdell, & Hagger-Johnson, 2012), and therefore its positive effect on the actor's change-oriented behaviors, including voice, might not be as prominent. Existing research, however, has suggested that compared with negative emotions, positive emotions are fewer in number and more diffuse (de Rivera et al, 1989;Ellsworth & Smith, 1988;Fredrickson, 1998). This may alleviate, to a certain degree, the concern that the findings obtained in our study cannot be generalized to other positive emotions.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 41%
See 2 more Smart Citations
“…A less activated positive emotion, for example, might signal the target's satisfaction with the status quo (Bindl, Parker, Totterdell, & Hagger-Johnson, 2012), and therefore its positive effect on the actor's change-oriented behaviors, including voice, might not be as prominent. Existing research, however, has suggested that compared with negative emotions, positive emotions are fewer in number and more diffuse (de Rivera et al, 1989;Ellsworth & Smith, 1988;Fredrickson, 1998). This may alleviate, to a certain degree, the concern that the findings obtained in our study cannot be generalized to other positive emotions.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 41%
“…Positive and negative affect is quite different in their characteristics, social meanings, and functions (e.g., Fredrickson, 1998;Forgas & George, 2001;. In addition, the states comprising negative affect are more differentiated than the states comprising positive affect (e.g., de Rivera et al, 1989;Ellsworth & Smith, 1988;Fredrickson, 1998). Therefore, in the following we first propose hypotheses on leaders' positive affect and then raise several research questions related to leaders' negative affect.…”
Section: Voice and The Emotion-as-social-information Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Although little is known about the subjective experience of the Japanese positive emotions, we already know quite a bit about the positive emotional experiences we have labeled in English. For example, studies by Lindsay-Hartz (1981) and by de Rivera, Possell, Verette, and Weiner (1989) have distinguished what occurs in joy, gladness, and elation. Of course, different people may use emotion labels somewhat differently.…”
mentioning
confidence: 99%
“…However, the broader emotion literature notes that positive affect can vary according to its level of activation (i.e., activated positive affect and unactivated positive affect) and that different levels of activation may lead to specific types of action . Unactivated positive affect (e.g., feeling relaxed), for example, may trigger reflection and a tendency to see connections, whereas activated positive affective (e.g., feeling excited) may lead to approach behavior requiring more effort or energy, such as exploration (De Rivera, Possel, Verette, & Weiner, 1989;. Thus, unactivated positive affect may inspire approach-oriented, prosocial action ), but only if such action does not require much energy or effort to achieve (De Rivera et al, 1989;.…”
Section: Daily Affect and Pro-environmental Behavior: Proposed Relatimentioning
confidence: 99%